Zinc-containing biological ceramic self-adhesive hydrogel as well as preparation method and application thereof in prevention and treatment of ventricular wall tumors
By adhering to and slowly releasing bioactive ions on the surface of the heart, the zinc-containing bioceramic hydrogels are solved, and the problem that the prior art cannot reverse the thinning of the ventricular wall after myocardial infarction is achieved, and the effect of preventing and treating ventricular wall tumors is achieved.
Patent Information
- Application Number
- CN202411852398.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-25
AI Technical Summary
Existing drugs for treating ventricular wall tumors cannot reverse the thinning of the ventricular wall after myocardial infarction, resulting in poor treatment results.
Using zinc-containing bioceramic hydrogel, the thinning of the left ventricular wall after myocardial infarction is reversed by adhering to and slowly releasing bioactive Zn2+ and SiO32-ions on the surface of the damaged heart.
Effectively prevent and/or treat ventricular wall tumors, improve cardiac function after myocardial infarction, and reverse the thinning of the left ventricular wall after myocardial infarction.
Smart Images

Figure CN119868409A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomedicine technology, and more specifically, relates to a zinc-containing bioceramic self-adhesive hydrogel, a preparation method thereof, and an application thereof in preventing and treating ventricular aneurysm. Background Art
[0002] Heart failure caused by myocardial infarction (MI) has become a serious clinical syndrome, posing a serious threat to the survival rate of patients. Among them, left ventricular aneurysm (VA) is one of the critical complications of late MI, with a mortality rate 50% higher than that of simple MI patients, posing a great threat to the life safety of patients.
[0003] The formation of ventricular aneurysm can lead to abnormal ventricular wall motion, ventricular wall thinning, ventricular cavity enlargement and cardiac systolic dysfunction, which are key factors in the progression of myocardial infarction to heart failure. Although there has been some progress in the clinical treatment of heart failure after ventricular aneurysm, the treatment effect is still unsatisfactory. Therefore, it is particularly urgent to find new treatment strategies for the pathophysiological process of ventricular aneurysm formation.
[0004] Ventricular aneurysm and heart failure share a common pathological mechanism, namely, the proliferation of fibroblasts and their transformation into myofibroblasts in response to myocardial injury, which in turn forms an adynamic scar, which further exacerbates the ineffective pumping of the myocardium. Adynamic scars seriously affect the contractile function of the left ventricle and may cause life-threatening conditions such as thrombosis, ventricular arrhythmias, and even local rupture of ventricular aneurysm.
[0005] As a new treatment method, engineered functional heart patches are made of biomaterials loaded / unloaded with cells, cytokines, drugs and other active substances. It not only provides structural support for damaged myocardium and helps the heart pump blood more efficiently, but also releases effective factors to stimulate the repair and regeneration of heart cells. However, relying solely on mechanical support provided by heart patches is far from enough for the repair and treatment of ventricular aneurysms. Therefore, constructing a heart patch that can slowly release effective bioactive factors may provide a new treatment idea for repairing damaged hearts, reversing pathophysiological processes, and preventing the occurrence of terminal malignant events.
[0006] However, although the prior art discloses that zinc silicate has the effects of promoting endothelial cell angiogenesis, inhibiting oxidative stress and myocardial cell apoptosis, improving cardiac function and preventing further damage, it has not been proven to be able to directly reverse the myocardial lesions that have already occurred, such as reversing the thinning of the ventricular wall caused by fibroblast proliferation and activation after myocardial infarction. At the same time, clinically commonly used myocardial protective drugs such as beta-blockers can reduce cardiac load and improve cardiac function, but studies have shown that their long-term clinical benefits for patients with myocardial infarction are still unclear (Argulian E, Bangalore S, Messerli F H. Misconceptions and facts about beta-blockers [J]. The American journal of medicine, 2019, 132 (7): 816-819.).
[0007] In summary, there is an urgent need to develop a drug or method that can treat or prevent ventricular aneurysm. Summary of the invention
[0008] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of existing drugs for treating ventricular aneurysms, whose therapeutic goal is to reduce cardiac load and improve cardiac function, but cannot reverse the thinning of the ventricular wall after myocardial infarction, thereby achieving the purpose of treating ventricular aneurysms, and provide the use of Zn2SiO4 in the preparation of drugs for treating and / or preventing ventricular aneurysms.
[0009] The purpose of the invention is to provide a zinc-containing bioceramic hydrogel.
[0010] Another object of the present invention is to provide a zinc-containing bioceramic hydrogel precursor.
[0011] Another object of the present invention is to provide the zinc-containing bioceramic hydrogel.
[0012] Another object of the present invention is to provide a method for preparing the zinc-containing bioceramic hydrogel.
[0013] Another object of the present invention is to provide the use of the zinc-containing bioceramic hydrogel precursor gel or the zinc-containing bioceramic hydrogel in the preparation of drugs for treating and / or preventing ventricular aneurysms.
[0014] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0015] The invention protects the application of Zn2SiO4 in preparing medicine for treating and / or preventing ventricular aneurysm.
[0016] Furthermore, the cell administration concentration of Zn2SiO4 is 1-50 mg / mL, which mainly refers to the concentration of Zn2SiO4 in liquid culture medium.
[0017] Preferably, the cell administration concentration of Zn2SiO4 is 1-5 mg / mL, more preferably 2-4 mg / mL.
[0018] The present invention protects a zinc-containing bioceramic hydrogel precursor gel, wherein the zinc-containing bioceramic hydrogel precursor gel comprises gelatin-hyaluronic acid hydrogel precursor gel and Zn2SiO4;
[0019] Wherein, the gelatin is unmodified gelatin or photosensitive gelatin; the hyaluronic acid is unmodified hyaluronic acid or photosensitive hyaluronic acid; and at least one of the gelatin and hyaluronic acid is a photosensitive material.
[0020] The inventor team first clarified the dual bioactive ions (SiO3 2- and Zn 2+ ) showed excellent synergistic effects in promoting endothelial cell proliferation and angiogenesis, inhibiting cardiomyocyte apoptosis, and protecting cardiomyocyte mitochondria from damage induced by reactive oxygen species. However, the mechanism of zinc silicate in intercellular conversion and affecting fibroblast proliferation and activation has not been studied, and its effect cannot be confirmed. It is even more impossible to confirm whether it can reverse the diseased ventricular aneurysm, which requires further exploration.
[0021] The present invention uses biodegradable gelatin and hyaluronic acid with good biocompatibility to prepare a zinc-containing bioceramic hydrogel precursor glue, and the obtained zinc-containing bioceramic hydrogel precursor glue is adhered to the damaged heart surface, and the Zn2SiO4 bioactive ceramics therein slowly release the bioactive Zn in situ. 2+ and SiO3 2- Ions, local supplementation of trace elements in the damaged ventricular wall area, can reverse the thinning of the left ventricular wall after myocardial infarction, thereby achieving the purpose of preventing and / or treating ventricular aneurysm.
[0022] It should be noted that large-area myocardial infarction (thinning of the left ventricular wall caused by occlusion of the left anterior descending artery) is prone to cause ventricular aneurysm formation. Therefore, only the left ventricle is basically considered, and the right ventricle is rarely involved.
[0023] Furthermore, the precursor gel generally refers to a substance that can be converted into a colloid or a colloid-like form. Under certain conditions, such as ultraviolet light, the photosensitive groups such as methacryloyl groups of the substance undergo free radical polymerization to form a three-dimensional network structure, thereby solidifying into a hydrogel.
[0024] Furthermore, the photosensitive gelatin includes methacryloyl gelatin. As one of the most commonly used hydrogel materials, methacryloyl gelatin (GelMA) has the characteristics of both natural and synthetic biomaterials, a three-dimensional structure suitable for cell growth and differentiation, excellent biocompatibility and cell response characteristics, and can replace artificial basement membranes or other natural collagen hydrogels. In addition, GelMA has good rapid photocuring properties, its mechanical properties are adjustable, and the abundant active carboxyl, hydroxyl, amino and other groups on the polymer chain can be used for covalent or non-covalent modification and connection of other adhesive components, and can be used to construct adhesive hydrogel systems.
[0025] Further, the photosensitive hyaluronic acid includes methacryloyl hyaluronic acid. Hyaluronic acid (HA) is the main component of the extracellular matrix, which is widely present in the human body, has low immunogenicity, clear metabolites, high biocompatibility and high safety. Hyaluronic acid can be combined with other photosensitive materials to prepare photosensitive materials. The carboxyl and hydroxyl groups of HA can also be methacrylated to generate cross-linked methacryloyl hyaluronic acid (HAMA), which is also photosensitivity and can further increase the viscosity of gelatin.
[0026] As an optional solution, the hyaluronic acid of the present application is non-modified hyaluronic acid.
[0027] Furthermore, the hyaluronic acid includes pharmaceutically acceptable salts thereof, such as common sodium hyaluronate.
[0028] Furthermore, the zinc-containing bioceramic hydrogel precursor gel is obtained by a preparation method comprising the following steps: in a light-proof condition, gelatin-hyaluronic acid hydrogel precursor gel is fully mixed with Zn2SiO4 to obtain the zinc-containing bioceramic hydrogel precursor gel.
[0029] Preferably, the mixing ratio of Zn2SiO4 and gelatin-hyaluronic acid hydrogel precursor is (20-30):1 mg / mL, more preferably 20:1 mg / mL.
[0030] Furthermore, the mass ratio of gelatin to hyaluronic acid is (5-10):1, more preferably (8-10):1, and most preferably 10:1.
[0031] Furthermore, the mass concentration of the gelatin is 50 to 300 mg / mL, more preferably 50 to 100 mg / mL, and most preferably 50 mg / mL.
[0032] Furthermore, in the gelatin-hyaluronic acid hydrogel precursor mixed solution, the mass concentration of the hyaluronic acid is 5 to 10 mg / mL, more preferably 5 to 8 mg / mL, and more preferably 5 mg / mL.
[0033] Furthermore, the gelatin-hyaluronic acid hydrogel precursor is obtained by a preparation method comprising the following steps: preparing a gelatin precursor under light-proof conditions, adding hyaluronic acid thereto, and mixing thoroughly to obtain the gelatin-hyaluronic acid hydrogel precursor.
[0034] Further, as a common implementation, the gelatin-hyaluronic acid hydrogel precursor is a sterilized gelatin-hyaluronic acid hydrogel precursor, which can be sterilized according to the actual application scenario.
[0035] Furthermore, the sterilization process is sterilization using a sterile syringe filter.
[0036] Furthermore, the pore size of the sterile syringe filter is 220-400 nm, preferably 220 nm.
[0037] Furthermore, the gelatin precursor is obtained by a preparation method comprising the following steps: gelatin and an initiator solution are fully mixed under light-proof conditions to obtain the gelatin precursor.
[0038] Furthermore, the initiator includes lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP).
[0039] Furthermore, the concentration of the initiator is 0.1-0.3% (w / v), more preferably 0.25% (w / v).
[0040] Furthermore, the conditions for sufficient mixing include shaking and water bath heating.
[0041] Furthermore, the water bath heating temperature is 60-70° C., and the water bath heating time is 20-30 min.
[0042] Specifically, the gelatin precursor is obtained by a preparation method comprising the following steps: mixing gelatin and an initiator solution under light-proof conditions, shaking to allow the gelatin to be fully soaked, heating and dissolving in a water bath at 60-70° C. for 20-30 minutes, shaking 3-4 times during the process, to obtain the gelatin precursor.
[0043] The present invention protects a zinc-containing bioceramic hydrogel, which comprises a gelatin-hyaluronic acid hydrogel and Zn2SiO4 loaded therein;
[0044] Wherein, the gelatin is unmodified gelatin or photosensitive gelatin; the hyaluronic acid is unmodified hyaluronic acid or photosensitive hyaluronic acid; and at least one of the gelatin and hyaluronic acid is a photosensitive material.
[0045] The invention discloses a method for preparing the zinc-containing bioceramic hydrogel, comprising the following steps: subjecting the zinc-containing bioceramic hydrogel precursor gel to a photo-crosslinking reaction under ultraviolet light irradiation to obtain the zinc-containing bioceramic hydrogel.
[0046] The present invention uses biocompatible, degradable gelatin and hyaluronic acid to prepare a zinc-containing bioceramic hydrogel precursor glue, and the obtained zinc-containing bioceramic hydrogel precursor glue is adhered to the damaged heart surface. The hydrogel precursor adheres to the surface of the damaged part of the heart after UV curing to construct a functional hydrogel heart patch, which provides a mechanical support for the gradually enlarged ventricular wall after myocardial infarction. At the same time, the Zn2SiO4 bioactive ceramic slowly releases the bioactive Zn 2+ and SiO3 2- Ions can locally supplement trace elements in the damaged ventricular wall area, prevent the formation of ventricular aneurysm after myocardial infarction, improve cardiac function after myocardial infarction, or reverse the thinning of the left ventricular wall after myocardial infarction, thereby achieving the purpose of preventing and / or treating ventricular aneurysm.
[0047] Furthermore, the wavelength of the ultraviolet light is 365-405 nm, preferably 405 nm.
[0048] Furthermore, the ultraviolet light irradiation distance is 8 to 12 cm, preferably 10 cm.
[0049] Furthermore, the ultraviolet light irradiation time is 10 to 15 seconds, preferably 10 seconds.
[0050] The present invention also protects the use of the zinc-containing bioceramic hydrogel precursor gel or the zinc-containing bioceramic hydrogel in preparing a drug for treating and / or preventing ventricular aneurysm.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] The present invention uses a biodegradable material with good biocompatibility to prepare a zinc-containing bioceramic hydrogel precursor gel, and applies the obtained zinc-containing bioceramic hydrogel precursor gel to the damaged heart surface. The hydrogel precursor adheres to the surface of the damaged part of the heart after being cured by ultraviolet light, thereby constructing a zinc-containing bioceramic hydrogel. The good elasticity of the hydrogel adapts to the periodic movement and strain of the heart, effectively prevents the unlimited expansion of the ventricle, and slowly releases the bioactive ceramic ion Zn in situ. 2+ and SiO3 2- , effectively reverse the proliferation and transformation of fibroblasts, prevent the formation of ventricular aneurysm after myocardial infarction, improve cardiac function after myocardial infarction, or reverse the thinning of the left ventricular wall after myocardial infarction, thereby achieving the purpose of preventing and / or treating ventricular aneurysm. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is the appearance of the two hydrogel precursors HA / GelMA and Zn2SiO4@HA / GelMA after being bonded to form a solid state after UV curing.
[0054] Figure 2 Data statistics of SEM images (A), element energy spectrum analysis and element distribution table (B) of two hydrogels HA / GelMA and Zn2SiO4@HA / GelMA; size, 50μm.
[0055] Figure 3 Stress-strain diagrams of HA / GelMA and Zn2SiO4@HA / GelMA.
[0056] Figure 4 Statistical graphs of the storage modulus G' and loss modulus G" of HA / GelMA and Zn2SiO4@HA / GelMA hydrogels as a function of time (A) and frequency (B).
[0057] Figure 5 For SiO3 in Zn2SiO4@HA / GelMA 2- (A) and Zn 2+ (B) Release curve diagram of the .
[0058] Figure 6 This is a statistical graph of the concentrations of the two ions in various tissues and serum of normal mice.
[0059] Figure 7 The concentrations of two ions (Zn 2+ and SiO3 2- ) concentration data.
[0060] Figure 8 Representative images of cardiac MRI in each group of mice (A); RV, right ventricle; LV, left ventricle; the red curve represents the location of LV; Sap, vertex area; Sat, vertex triangle area. Statistics of left ventricular ACR in each group of mice (B); * indicates P < 0.05, ** indicates P < 0.01, and *** indicates P < 0.001.
[0061] Fig. 9 The figure is the survival rate curve of mice in each group; * indicates P < 0.05, and ns indicates no statistical difference.
[0062] Fig.10Representative B-Mode and M-Mode echocardiograms of the hearts of mice in each group 28 days after myocardial infarction (A), as well as EF (B), FS (C), LVIDs (D), and LVIDd (E); * indicates P < 0.05, ** indicates P < 0.01, *** indicates P < 0.001, and ns indicates no statistical difference.
[0063] Fig.11 Representative images of the heart samples taken 28 days after myocardial infarction in each group of mice, echocardiography M-mode images, endocardial radial myocardial motion trajectory, and endocardial global longitudinal strain (A), as well as GLS (B), GCS (C), and GRS (D) statistical graphs of each group. * indicates P < 0.05, ** indicates P < 0.01, and *** indicates P < 0.001.
[0064] Fig.12 The heart weight to tibia length ratio (HW / TL) (A) and the heart weight to body weight ratio (HW / BW) (B) of mice in each group; * indicates P < 0.05, ** indicates P < 0.01, and *** indicates P < 0.001.
[0065] Fig.13 Representative images of Masson staining of heart sections 28 days after myocardial infarction in each group of mice (transverse and longitudinal (A), size, 1 mm and 50 μm (enlarged image) and fibrosis statistics and left ventricular thickness statistics (BC); * indicates P < 0.05, ** indicates P < 0.01, *** indicates P < 0.001.
[0066] Fig.14 Immunofluorescence staining images of Smad3, TGF-β (red), α-actinin (green), and DAPI (blue) in heart sections of mice in each group at day 28, with a size of 50 μm.
[0067] Fig.15 The data are statistical graphs showing the effects of different proportions of Zn2SiO4 extract on the viability of fibroblasts, where from left to right are the data statistical graphs showing the viability of fibroblasts for 2 hours (A); the viability of fibroblasts under normoxia (B) and hypoxia (C) for 24 hours; * indicates P<0.05, ** indicates P<0.01, and *** indicates P<0.001.
[0068] Fig.16Schematic diagram of the scratch experiment of fibroblasts in each treatment group under the hypoxia model (A) and the statistical graph of the relative migration speed after 24 hours (B), size, 250 μm; Schematic diagram of the scratch experiment of fibroblasts in each treatment group under the TGF-β induction model (C); and the statistical graph of the relative migration speed after 24 hours (D); size, 250 μm; * indicates P < 0.05, ** indicates P < 0.01, *** indicates P < 0.001.
[0069] Fig.17 Representative images of EdU staining of fibroblasts in each treatment group under the hypoxia model (A) and the corresponding fluorescence intensity statistical graph (B), size, 50 μm; representative images of EdU staining of fibroblasts in each treatment group under the TGF-β model (C) and the corresponding fluorescence intensity statistical graph (D), size, 50 μm; * indicates P < 0.05, ** indicates P < 0.01, and *** indicates P < 0.001.
[0070] Fig.18 Representative images of immunofluorescence staining of α-SMA and CollagenI in fibroblasts of each treatment group under the TGF-β model (A) and the corresponding fluorescence intensity statistical graphs (BC), size, 50 μm; * indicates P < 0.05, ** indicates P < 0.01, *** indicates P < 0.001.
[0071] Fig.19 WB images of CollagenI, α-SMA, MEOX1, and CTGF in fibroblasts of each treatment group (A) and grayscale statistical diagrams of the corresponding proteins (BE); * indicates P < 0.05, ** indicates P < 0.01, *** indicates P < 0.001, and ns indicates no statistical difference.
[0072] Fig. 20 Data statistical diagram of genomic functional analysis (GO analysis) (A) and KEGG pathway enrichment (B) of differentially expressed genes in fibroblasts under two treatments under the TGF-β model.
[0073] Fig.21 The data statistical chart of gene expression of fibroblasts under two treatments under the TGF-β model, including MEOX1, CollagenI, α-SMA, Hmgb3, CDK1, and CCNB1 genes; * indicates P<0.05, ** indicates P<0.01, and *** indicates P<0.001.
[0074] Fig. 22 Schematic diagram of the scratch test of fibroblasts under different treatments (A) and statistical diagram of migration area (B); * indicates P < 0.05, ** indicates P < 0.01, and *** indicates P < 0.001.
[0075] Fig.23 Schematic diagram of the migration experiment of fibroblasts under different treatments (A) and statistical diagram of the number of migrated cells (B); * indicates P < 0.05, ** indicates P < 0.01, and *** indicates P < 0.001. DETAILED DESCRIPTION
[0076] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0077] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0078] The methacryloyl gelatin in the embodiment is from Engineering For Life; the hyaluronic acid (HA) used in the embodiment is in the form of sodium salt of hyaluronic acid, which is derived from: sodium hyaluronate ≥ 98%, CAS number: 9067-32-7, molecular formula: (C 14 H 21 NaNO 11 ) n ; PubChem number: 23663392.
[0079] Figure 2 A means Figure 2 Figure A in Figure 2 B stands for Figure 2 The naming meanings of other figures are similar.
[0080] 0.25% (w / v) means that the mass concentration of the substance is 0.25% (w / v), which is 2.5 mg / mL, and the same applies to other contents.
[0081] Example 1 Preparation of hydrogels HA / GelMA and Zn2SiO4@HA / GelMA
[0082] Methacrylated gelatin GelMA was used to prepare Zn2SiO4 composite hydrogel, named Zn2SiO4@HA / GelMA group, while GelMA alone was used as the control group, named HA / GelMA group. The specific preparation process is as follows: First, GelMA precursor gel was prepared, that is, 0.25% (w / v) standard solution of photoinitiator LAP was prepared, and the required mass of GelMA was put into a centrifuge tube at a ratio of 5% (w / v) and the above initiator standard solution was added, and the GelMA was fully infiltrated by shaking, and heated in a water bath at 60-70°C away from light for 20-30 minutes, during which it was shaken 3-4 times, and HA powder was added at a ratio of 0.5% (w / v) to prepare HA / GelMA precursor gel, and finally the obtained HA / GelMA precursor gel was immediately sterilized with a 0.22μm sterile syringe filter. 1 mL of sterilized HA / GelMA precursor gel was added with 20 mg of Zn2SiO4 powder to prepare Zn2SiO4@HA / GelMA precursor gel. After the two precursor gels were prepared, they were irradiated under a 405 nm UV lamp (at a distance of about 10 cm) for about 10 seconds to solidify into two hydrogels HA / GelMA and Zn2SiO4@HA / GelMA (such as Figure 1 shown).
[0083] Example 2 Morphology and energy spectrum analysis of hydrogel
[0084] The morphology and structure of the two hydrogels obtained in Example 1 were observed using a field emission scanning electron microscope. At the same time, the present invention used the surface scanning function of the energy spectrometer to conduct detailed detection of the various element components, contents and distributions in the two hydrogels. The results are as follows: Figure 2 A Results show that both HA / GelMA and Zn2SiO4@HA / GelMA present honeycomb structures. Figure 2 As shown in Figure B, HA / GelMA mainly contains C, Na, and O, while the content of Zn and Si is 0. In contrast, the content of Zn and Si in Zn2SiO4@HA / GelMA is 5.8% and 0.47% (wt%), respectively.
[0085] Example 3 Determination of mechanical properties of hydrogel
[0086] An electronic universal testing machine (Shenzhen Sansi SANS-UTM5300H) was used to determine the performance of the two hydrogels obtained in Example 1 under an applied fracture load. A stress-strain diagram was obtained by applying compressive pressure to the sample using a pressure plate or a special tool on a universal testing machine to determine the elastic limit, proportional limit, yield point, yield strength and (for some materials) compressive strength of the two hydrogels.
[0087] The results are as follows Figure 3The results show that HA / GelMA and Zn2SiO4@HA / GelMA show a trend of increasing stress at a strain of about 70%, indicating that the elastic limit and compressive strength points of the two hydrogels are at a strain of about 70%. The stress-strain trends of the two are similar, which shows that the addition of Zn2SiO4 does not change the compressive capacity of HA / GelMA.
[0088] In order to detect the rheological properties of the two hydrogels obtained in Example 1 after UV curing, an advanced rotational rheometer (Thermo Fisher Scientific MARS 40) was used to apply a certain stress load to the hydrogel sample to observe the response data of the sample to the applied load; by measuring rheological data such as shear rate, shear stress, oscillation frequency, stress-strain amplitude, etc., the storage modulus G' and loss modulus G" of the sample were calculated to describe the flow and deformation characteristics of the solid hydrogel after curing.
[0089] The results are as follows Figure 4 The results show that G' of HA / GelMA and Zn2SiO4@HA / GelMA is greater than G", and neither changes with time. The G' and G" of HA / GelMA and Zn2SiO4@HA / GelMA at different frequency amplitudes remain basically unchanged. This shows that a stable solid hydrogel is formed after UV curing. In addition, the addition of Zn2SiO4 does not change the mechanical properties of HA / GelMA.
[0090] Example 4 Determination of release properties of hydrogel Zn2SiO4@HA / GelMA
[0091] In order to evaluate the ion release performance of the composite hydrogel Zn2SiO4@HA / GelMA obtained in Example 1, 1 g of the hydrogel was added to 10 mL of phosphate buffered saline (PBS buffer). Then, at the preset time points, i.e., days 1, 2, 3, 4, 14, and 28, the suspension was centrifuged at 4000 rpm for 10 minutes to collect the released ion-containing supernatant. Subsequently, the original solution was replaced with 10 mL of fresh PBS solution. In order to accurately determine the Zn 2+ and SiO3 2- The concentration of ions was analyzed by ion chromatography-atomic emission spectrometry (ICP-AES; Thermo Fisher X Series 2, USA).
[0092] The results are as follows Figure 5 The results showed that Zn2SiO4@HA / GelMA can release ions for a long time within 28 days. 2- ( Figure 5 A) and Zn 2+ ( Figure 5B) Rapid release within the first 7 days, with SiO3 2- The release amount can reach 67μg / mL, Zn 2+ The release of SiO3 2- and Zn 2+ The ion release rate of SiO3 2- The cumulative release of Zn 2+ The cumulative release of SiO3 reached 38.86 μg / mL. 2- The release amount was still higher than 0.8 μg / mL, while Zn 2+ The release amounts were also higher than 0.2 μg / mL, and these release amounts were maintained within the bioactive concentration range.
[0093] Example 5 Ion distribution of hydrogel Zn2SiO4@HA / GelMA after treatment
[0094] In order to evaluate the distribution of ions in animal tissues after treatment with the composite hydrogel Zn2SiO4@HA / GelMA obtained in Example 1, the visceral tissues (heart, liver, spleen, lungs and kidneys) and blood of mice were collected on days 1, 7, 14 and 28 after myocardial infarction modeling. The visceral tissues of each group were digested with aqua regia (HCl:HNO3=3:1). The digestion solution was centrifuged (4000rad / s), the supernatant was collected, and diluted with deionized water to an appropriate concentration. In addition, the blood was also diluted with deionized water. At the same time, standard solutions of each gradient of the ions to be tested were set, and ICP-AES (Thermo Fisher X Series 2, USA) was used to determine the Zn in the standard solution and the solution to be tested. 2+ and SiO3 2- Previous studies have shown that SiO3 2- The ion concentration is 10μg / g and SiO3 in the lungs 2- The ion concentration of 120μg / g is safe. 2+ The ion concentration of Zn in mouse liver is about 20μg / g. 2+ The ion concentration is about 30μg / g.
[0095] The results are as follows Figure 6 The concentrations of the two ions in each tissue and serum of normal mice are shown. In order to detect whether the application of the hydrogel causes high concentrations of ions to cause toxicity to other organs, the present invention detected the ion concentrations in each organ, and the results are shown as follows: Figure 7As shown, the Zn2SiO4@HA / GelMA group mice in the heart, liver, spleen, lung, kidney, and blood at D1 and D7 showed significant differences in Zn 2+ and SiO3 2- The concentration was significantly higher than that of the other two groups. The concentrations of the two ions in the internal organs of the other two groups were similar to those of normal mice. In addition, after 14 days of treatment with Zn2SiO4@HA / GelMA, there was no significant difference in the concentrations of the two ions in tissues and blood between the MI group and the HA / GelMA group, and the ion concentrations of each group of mice were similar to those of the normal group. This shows that the ions in the hydrogel have been completely released after 14 days, and the concentrations of the two ions in each group are within the normal range. The treatment with the hydrogel did not cause excessive load and toxicity of ions in the body.
[0096] Example 6 Application of hydrogel Zn2SiO4@HA / GelMA in preventing ventricular aneurysm formation, a late complication of malignant myocardial infarction.
[0097] 1. Zn2SiO4@HA / GelMA cardiac patch prevents ventricular aneurysm formation and reduces mortality in mice
[0098] (1) Establishment of mouse myocardial infarction model: 1% sodium pentobarbital at a dose of 0.1 mL / 20 g was intraperitoneally injected into the mouse for anesthesia. After complete anesthesia, the hair on the front chest was removed and the head and limbs were fixed on the operating table; the mouse tongue was lifted, the tracheal opening was found under the LED light, and the intravenous indwelling needle was gently inserted into the trachea, the needle core was withdrawn, the indwelling needle was fixed, and the other end was connected to the small animal ventilator and the parameters were set; the mouse was adjusted to the right side lying position, the skin was cut between the 3rd and 4th ribs, the muscles were separated layer by layer, and the intercostal space was carefully opened to expose the heart; an 8-0 suture with a needle was inserted 2 to 3 mm below the lower end of the left auricle, a part of the myocardium was hooked and a surgical knot was quickly tied; when it was observed that the anterior wall of the left ventricle below the ligature line turned pale, it could be determined that the myocardial infarction model was successfully established. Then, 30 μL of HA / GelMA and Zn2SiO4@HA / GelMA glue was applied near the ligature with a pipette, and irradiated with UV light for about 10 seconds at a distance of 10 cm to solidify into glue to form a heart patch. The chest cavity was closed, and the ventilator was turned off after the mouse recovered spontaneous breathing, the endotracheal tube was removed, the ear tag was placed under a physiotherapy lamp at an appropriate temperature for 12 hours, and the mouse was transferred to a regular animal breeding room after normal activity.
[0099] (2) Mice were divided into three groups: Sham group, MI group, HA / GelMA group and Zn2SiO4@HA / GelMA group. The Sham group was normal mice; the MI group was mice with simple myocardial infarction; the HA / GelMA group was mice with myocardial infarction and 20-30 μL HA / GelMA was applied on the surface of the infarcted myocardium; the Zn2SiO4@HA / GelMA group was mice with myocardial infarction and 20-30 μL Zn2SiO4@HA / GelMA was applied on the surface of the infarcted myocardium.
[0100] (3) To further evaluate the morphology of the ventricular wall muscle layer and each chamber of the mouse, MRI examination of the mouse heart was performed 28 days after myocardial infarction in the mouse using a small animal magnetic resonance imaging system (PharmaScan70 / 16US). First, the experimental mouse was pre-anesthetized until the mouse took a slow and deep breath, and the mouse was quickly placed on the animal bed in a supine position. The animal was installed with a suitable coil, and the gas line, mask, and ECG monitoring line were connected to monitor the mouse's breathing and ECG morphology. After the laser was moved and positioned, the test conditions of the instrument were checked to be qualified, and then the software on the operating table computer was opened and the appropriate sequence was selected for scanning. The relevant acquired images were viewed and analyzed using the RadiAnt DICOM Viewer.
[0101] The results are as follows Figure 8 As shown, the results of cardiac MRI showed that the anterior and posterior walls of the ventricle of mice in the Sham group were obvious and the thickness of the muscle wall was normal; the anterior wall of the left ventricle in the MI group was thinned (blue arrow), the muscle wall shadow was blurred and thinned, the left ventricular cavity was enlarged, the anterior wall of the left ventricle bulged with the heart beat, and the apex became blunt, indicating the formation of ventricular aneurysm; the anterior wall of the ventricle in the treatment group was thinned, but the bulging of the left ventricular muscle wall with the heart beat was smaller than that in the MI group; it can be seen from the heart CINE that the blood flow in the left ventricle of each modeling group showed signs of circuitous stagnation at the apex. It can be seen that ventricular aneurysm was formed in each modeling group, and the hydrogel treatment group reduced the range of the fibrous wall of the ventricular aneurysm.
[0102] (4) During the observation period, the survival rate of mice in each group was recorded and compared. The results were as follows: Fig. 9 As shown in the figure, the survival curve shows that mice in each group died within 7 days after myocardial infarction; the mortality rate of mice in the MI group was higher than 50%; compared with the MI group, the HA / GelMA group (68.75% vs 45%) and the Zn2SiO4@HA / GelMA group (80% vs 45%) can improve the survival rate of mice after myocardial infarction to a certain extent; among them, the Zn2SiO4@HA / GelMA group improved the survival rate of mice with statistical significance. It can be seen that the hydrogel Zn2SiO4@HA / GelMA as a heart patch can improve the survival rate of mice with myocardial infarction.
[0103] 2. Zn2SiO4@HA / GelMA cardiac patch improves cardiac function in mice after myocardial infarction
[0104] (1) To detect the effect of the cardiac patch on the cardiac function of mice, the present invention performed cardiac ultrasound (Vevo 3100LT, VisualSonics, USA) on the mice on the 28th day after myocardial infarction to evaluate the cardiac function of the mice after infarction. The ejection function and diastolic function of the mice were evaluated by comparing the LVEF, LVFS, LVIDs, LVIDd, and LV volumes during systole and diastole of the mice.
[0105] The results are as follows Fig.10 As shown, the B-mode and M-mode images of mice in each group showed that the heart cavity of the MI group was significantly enlarged and the ventricular wall was thinner than that of the normal group; the hydrogel treatment group was able to reverse this trend, among which the Zn2SiO4@HA / GelMA group had a stronger ability to reverse the enlargement of the ventricular cavity and the thinning of the ventricular wall; in the statistics of the cardiac function indexes of each group (including LVEF, LVFS, LVIDd, and LVIDs), the LVEF and LVFS of the MI group were significantly lower than those of the normal group, the LVIDs were higher than those of the normal group, and there was no statistically significant difference in LVIDd among the groups. The HA / GelMA group could improve the EF value after myocardial infarction to a certain extent, and the Zn2SiO4@HA / GelMA group could significantly improve various cardiac function indicators of mice.
[0106] (2) To detect the effect of the cardiac patch on the contraction and relaxation function, blood supply, myocardial vitality, etc. of the local myocardium of mice. The present invention performed ultrasonic speckle tracking analysis on each group of mice 56 days after myocardial infarction in mice. Speckle tracking echocardiography can calculate the strain of myocardial tissue by measuring the displacement of tissue. Myocardial strain refers to the extremely small deformation of the myocardium under the action of external force, which can be used to evaluate the contraction and relaxation function, blood supply, myocardial vitality, etc. of the local myocardium. VEVO Lab (Fujifilm Visual Acoustics) was used to perform two-dimensional (B-mode) parasternal long-axis and short-axis echocardiography. Three consecutive cardiac cycles were selected in the B-mode echocardiography, and the area where the R wave was clearly visible on the two-dimensional image was analyzed. The boundaries of the endocardium and the epicardium were manually outlined, and the relevant parameters of the endocardium and the epicardium were measured in the longitudinal and circumferential axial planes. The measurement indicators include: left ventricular global longitudinal strain peak (GLS), global radial strain peak (GRS) and global circumferential strain peak (GCS), and the relevant parameters were statistically analyzed.
[0107] The results are as follows Fig.11As shown in A, B-Mode echocardiography showed that the ventricular walls of the three modeling groups were thinner than those of the Sham group, and the ventricular cavity became larger. The radial motion trajectory diagram and longitudinal strain representative diagram of the ventricular muscle wall showed that the myocardial motion of the Sham group showed a spiral morphology in both radial and longitudinal views, and had strong strain capacity. The myocardial motion trajectory of the MI group was irregular, and the strain capacity was significantly weakened. The myocardial motion trajectory of the Zn2SiO4@HA / GelMA group and the HA / GelMA group was improved compared with the MI group, and the strain force was improved. The Zn2SiO4@HA / GelMA group improved the myocardial motion trajectory and strain capacity of mice better than those of the HA / GelMA group. Quantitative analysis ( Fig.11 B-D) showed that compared with the Sham group, the left ventricular myocardial strain was significantly impaired in the MI group, as manifested by smaller endocardial GLS (23.076%±6.847% vs 3.432%±1.939%), epicardial GLS (11.075%±3.368% vs 1.665%±0.61%), endocardial GCS (28.684%±8.058% vs 5.965%±1.626%), epicardial GCS (9.021%±0.627% vs 3.313%±1%), longitudinal GRS (30.7%±1.721% vs 4.101%±2.365%), and circumferential GRS (33.992%±7.359% vs 7.047%±4.136%). The Zn2SiO4@HA / GelMA group reversed the trend of significant strain impairment caused by myocardial infarction; the longitudinal total radial strain GRS of the HA / GelMA group was improved compared with the MI group (10.426%±5.66% vs 4.101%±2.365%), but there was no statistically significant improvement in the endocardial and epicardial GLS, endocardial and epicardial GCS, and circumferential GRS compared with the MI group.
[0108] 3. Zn2SiO4@HA / GelMA cardiac patch improves ventricular remodeling after myocardial infarction in mice
[0109] (1) To evaluate the effect of cardiac patch therapy on the formation of dilated heart disease after myocardial infarction in each group of mice, the present invention recorded the body weight, heart weight and tibia length of the mice after the observation period, and compared the heart weight of each group of mice to evaluate the cardiac remodeling of the mice.
[0110] The results are as follows Fig.12 As shown, the HW / BW ( Fig.12 B) HW / TL( Fig.12 A) was significantly higher than that of the normal group; the HA / GelMA group could reduce the HW / BW of mice to a certain extent, and the Zn2SiO4@HA / GelMA group could significantly reverse the increase of HW / BW and HW / TL.
[0111] (2) Grouping and Experiments Referring to Parts 1 and 2 of Example 6, in order to evaluate the effects of each treatment group on the left ventricular wall thickness and degree of fibrosis in mice, paraffin sections of mouse hearts were made after 28 days of treatment, and the sections of each group were stained with Masson staining. They were photographed using an inverted microscope, and ventricular remodeling was analyzed using Image J software.
[0112] The results are as follows Fig.13 Shown are representative images of Masson-stained longitudinal and transverse sections ( Fig.13 A) shows that the left ventricular wall of the MI group mice was significantly thinner than that of the Sham group, and the apex was bulging and rounded. The Zn2SiO4@HA / GelMA group was able to reverse the thinning of the ventricular wall after myocardial infarction, as shown by a decrease in the degree of fibrosis ( Fig.13 B), the left ventricular wall thickness was thicker than that of the MI group ( Fig.13 C). The HA / GelMA group was able to reduce the degree of left ventricular fibrosis to a certain extent, but failed to reverse the thinning of the left ventricular wall after myocardial infarction. The results showed that Zn2SiO4@HA / GelMA hydrogel treatment can effectively prevent adverse left ventricular remodeling after myocardial infarction in mice and improve cardiac function after infarction.
[0113] (3) To verify whether the hydrogel affects fibrosis after myocardial infarction in mice through the classical fibrosis pathway, heart sections from each group were taken 4 weeks after myocardial infarction for TGF-β and Smad3 staining. The tissue sections were fixed and blocked, and then stained with primary antibodies overnight at low temperature. The next day, they were stained with corresponding secondary antibodies, and finally, the cell nuclei were stained with DAPI.
[0114] The results are as follows Fig.14 As shown in the figure, the expression levels of TGF-β and Smad3 in the hearts of mice in the MI group were significantly higher than those in the Sham group; the Zn2SiO4@HA / GelMA group was able to reduce the expression levels of these two proteins after myocardial infarction. However, there was no significant difference in the expression levels of TGF-β and Smad3 in the HA / GelMA group. This shows that the ions released by Zn2SiO4 in the hydrogel Zn2SiO4@HA / GelMA affect the protein expression levels on the classical TGF-β / Smad3 pathway after hypoxic injury of fibroblasts, thereby affecting the degree of fibrosis after myocardial infarction, while this effect was not observed in the HA / GelMA group.
[0115] Example 7 Application of Bioactive Ceramic Zn2SiO4 Extract in Proliferation and Activation of Cardiac Fibroblasts
[0116] 1. Zn2SiO4 extract inhibits the proliferation of fibroblasts
[0117] (1) Preparation of Zn2SiO4 extract
[0118] 1 g Zn2SiO4 bioceramic powder (Shanghai Institute of Silicates) was dissolved in 5 mL serum-free high-glucose Dulbecco's modified eagle medium (DMEM) (Gibco, USA) or normal saline and incubated in a shaker (120 rpm min -1 ) and incubated at 37°C for 24 h. The suspension was centrifuged at 4000 rpm for 5 min and sterilized using a 0.22 μm filter (Millipore, USA). The Zn2SiO4 extract dissolved in DMEM was diluted in DMEM complete medium at different ratios (1 / 4, 1 / 8, 1 / 16, 1 / 32, 1 / 64, 1 / 128) for cell experiments.
[0119] (2) Extraction, culture and model construction of mouse primary cardiac fibroblasts
[0120] Cardiac fibroblasts were isolated by extracting mouse neonatal cardiomyocytes. The cardiac cells were digested with collagenase and seeded in a dish. Due to the different adhesion speeds between cardiac fibroblasts and cardiomyocytes, cardiac fibroblasts could be firmly attached to the culture dish after 2 hours. The cell culture medium was changed to DMEM culture medium containing 2-5% serum to culture cardiac fibroblasts. After the cell density reached 80%-90%, the cells were passaged for subsequent experiments.
[0121] (4) CCK8 assay to detect the viability of cardiac fibroblasts
[0122] To explore the SiO3 in Zn2SiO4 leaching solution 2- and Zn 2+ To determine whether it affects the proliferation and activation of fibroblasts, the present invention uses Zn2SiO4 extract to treat primary cardiac fibroblasts. Primary mouse cardiac fibroblasts were isolated from newborn mice and cultured at 1×10^ 3 The cells were inoculated in a 96-well plate at a density of 10 cells and cultured for 12 hours. Before the cardiac fibroblasts were placed in a cell culture incubator containing 1% oxygen to establish the injury model, the culture medium was replaced with a culture medium containing different concentrations (1 / 4, 1 / 8, 1 / 16, 1 / 32, 1 / 64, 1 / 128 and 1 / 256) of Zn2SiO4 extract. After 2 hours and 24 hours of hypoxia, the proliferation rate of primary cardiac fibroblasts under different treatments was detected using the CCK8 detection kit.
[0123] The results are as follows Fig.15 As shown in the results of the CCK8 experiment after 2 hours of treatment, the activity of fibroblasts with a concentration of more than 1 / 32 times was not different from that of the control group. The bioactive ceramic extract at a higher concentration (1 / 4, 1 / 8, 1 / 16) inhibited the activity of fibroblasts ( Fig.15A). The results of the cell CCK8 experiment after 24h treatment with different concentrations of extracts showed that 1 / 64Zn2SiO4 bioactive ceramic extracts could inhibit normoxic ( Fig.15 B) and hypoxia ( Fig.15 C) The proliferation rate of fibroblasts in the state. Since the pathological conditions will promote the proliferation of fibroblasts and promote cardiac fibrosis, the 1 / 64Zn2SiO4 bioactive ceramic extract can inhibit the proliferation of fibroblasts without causing toxicity to them, which is beneficial to slowing down the process of cardiac fibrosis. Therefore, in the subsequent cell experiments, the 1 / 64Zn2SiO4 extract was used to treat fibroblasts.
[0124] (5) Cell grouping: In the present invention, two methods, hypoxia (1% O2) and 10ng / ml TGF-β, were used as cell models to conduct cell experiments. The cell experiment groups were: 21% O2, 21% O2+Zn2SiO4, 1% O2, 1% O2+Zn2SiO4 or TGF-β(-), TGF-β(-)+Zn2SiO4, TGF-β(+), TGF-β(+)+Zn2SiO4. Among them, 21% O2+Zn2SiO4 means that cells are treated with 1 / 64Zn2SiO4 extract under normoxic conditions; TGF-β(+)+Zn2SiO4 means that 10ng / mlTGF-β is induced to induce cardiac fibroblasts and 1 / 64Zn2SiO4 extract is added at the same time.
[0125] (6) Fibroblast scratch test:
[0126] The cell experiment grouping is the same as that in part (5) of Example 7. Primary cardiac fibroblasts were seeded on a 6-well plate. When the fibroblast density reached 80% to 90%, the fibroblast monolayer was scraped off with a 200 μL pipette tip and washed with PBS to remove unattached cells. The fibroblasts in the 6-well plate were subjected to different treatments (hypoxia or TGF-β induction). The cardiac fibroblasts were imaged using an optical microscope at 0 h and 24 h after hypoxia.
[0127] like Fig.16 As shown, the scratch test results ( Fig.16 A) shows that after 24 hours of hypoxia, the migration and proliferation of fibroblasts increased significantly, while the migration and proliferation of fibroblasts treated with 1 / 64 Zn2SiO4 extract decreased; similarly, the migration and proliferation of fibroblasts treated with 1 / 64 Zn2SiO4 extract under normoxia were slower than those of the blank control group ( Fig.16B). In the TGF-β-induced activation model, 1 / 64 Zn2SiO4 extract can reduce the migration and proliferation rate of fibroblasts; similarly, 1 / 64 Zn2SiO4 extract can reduce the migration and proliferation rate of fibroblasts without induced activation ( Fig.16 C). It can be seen that 1 / 64 Zn2SiO4 extract can inhibit the proliferation of fibroblasts in normal and activated states.
[0128] (7) Fibroblast EdU cell immunofluorescence experiment
[0129] The cell experiment grouping was the same as that in part (5) of Example 7. The cells were fixed and blocked, stained with an EDU proliferation kit, and stained with DAPI for nuclei.
[0130] EdU proliferation staining results showed (eg Fig.17 A and Fig.17 C), 1 / 64Zn2SiO4 extract can reduce hypoxia ( Fig.17 B) and TGF-β-induced ( Fig.17 D) The expression of EdU proliferation markers in activated fibroblasts; similarly, 1 / 64 Zn2SiO4 extract can also reduce the expression of EdU proliferation markers in normal fibroblasts. This shows that 1 / 64 Zn2SiO4 extract can inhibit the proliferation of fibroblasts in normal and activated states.
[0131] 2. Zn2SiO4 extract inhibits the activation of fibroblasts
[0132] (1) Cell immunofluorescence staining
[0133] The cell experiment grouping is the same as that in part (5) of part 1 of Example 7. To detect the effect of 1 / 64 Zn2SiO4 extract on the expression of fibroblast activation markers. The cells were fixed and blocked, and stained with primary antibodies overnight at low temperature. The next day, they were stained with corresponding secondary antibodies, and finally, the cell nuclei were stained with DAPI. The primary antibodies included were: CollagenI, α-SMA.
[0134] The results are as follows Fig.18 As shown, the immunofluorescence results ( Fig.18 A) shows that Zn2SiO4 extract can inhibit the expression of α-SMA (a marker of fibroblast activation) regardless of whether fibroblasts are activated or not. Fig.18 B) and Collagen I ( Fig.18 C). It can be seen that 1 / 64Zn2SiO4 extract can inhibit the activation of fibroblasts in normal and activated states.
[0135] (2) Western blot (WB) experiment
[0136] The cell experiment grouping is the same as part (5) of part 1 in Example 7. The cardiac fibroblasts for the cell experiment were collected and ripa lysis buffer was added for protein extraction. After centrifugation, the supernatant was added to the loading buffer to prepare the protein loading solution. The expression levels of each protein in cells and tissues between different groups were detected by western blotting. The primary antibodies used in this study include: GAPDH, MEOX1, CTGF, CollagenI, and α-SMA.
[0137] The results are as follows Fig.19 As shown, WB results ( Fig.19 A) shows that Zn2SiO4 extract can reduce the expression of α-SMA (a marker of fibrosis) in fibroblasts with or without induction of activation. Fig.19 B) and Collagen I ( Fig.19 C); while Zn2SiO4 extract can reduce the expression of MEOX1( Fig.19 D) and CTGF ( Fig.19 E), but in fibroblasts without TGF-β induction, Zn2SiO4 extract failed to reduce the expression of MEOX1 and CTGF. This shows that Zn2SiO4 extract can reduce the expression of fibrotic marker proteins in fibroblasts, but reducing the expression of MEOX1 requires the participation of TGF-β, which once again verifies that MEOX1 mediates the TGF-β-induced fibroblast fibrosis response.
[0138] (3) Cell transcriptome sequencing analysis of the potential mechanism by which Zn2SiO4 extract inhibits fibroblast proliferation and activation
[0139] The inventor team first clarified the dual bioactive ions (SiO3 2- and Zn 2+ ) showed excellent synergistic effects in promoting endothelial cell proliferation and angiogenesis, inhibiting cardiomyocyte apoptosis, and protecting cardiomyocyte mitochondria from damage induced by reactive oxygen species. However, the mechanism of zinc silicate in intercellular conversion and affecting fibroblast proliferation and activation has not been studied and needs further exploration.
[0140] In order to further explore the potential mechanism of the bioactive ions in the Zn2SiO4 extract inhibiting the proliferation and activation of cardiac fibroblasts, the present invention analyzed the effect of the addition of Zn2SiO4 on the gene expression of fibroblasts induced by TGF-β by transcriptome sequencing. The groups were TGF-β(+), TGF-β(+)+Zn2SiO4. The cells in each group were collected using RNA extraction reagent (Eric Biology), and the quality of the collected cell samples was controlled and the library of the sample source was constructed. After the library was constructed, the insert size and effective concentration of the library were detected. After the library was qualified, different libraries were pooled according to the target sequencing data volume, and sequenced on the machine, including quantitative analysis of gene expression, analysis of gene differential expression, functional enrichment analysis, and gene structure analysis.
[0141] The results are as follows Fig. 20 The results showed that the downregulated DEG genes were enriched in cell cycle transition, epithelial-mesenchymal transition, DNA binding and other functions ( Fig. 20 A). KEGG pathway enrichment includes pathways such as ECM-receptor interaction. Downregulated genes include cell cycle-related genes, DNA binding-related genes, migration proteins, epidermal-mesenchymal transition genes, etc. ( Fig. 20 B).
[0142] Furthermore, QPCR was used to detect the expression of related fibroblast activation indicators and cell cycle-related genes, and the results showed that (e.g. Fig.21 ), MEOX1, CollagenI, α-SMA, Hmgb3, CDK1, and CCNB1 gene expression was downregulated, and the addition of Zn2SiO4 extract reduced the expression of fibroblast activation markers and cell cycle factors. The downregulation of fibrosis indicators was consistent with the results of the previous scratch test and immunofluorescence experiment.
[0143] Epithelial-mesenchymal transition is a cellular process, usually initiated by transforming growth factor β (TGF-β) family ligands. The single-cell mRNA sequencing results of a study analyzed the dynamic changes of various cardiac stromal cells after myocardial infarction, among which fibroblasts myogenically formed myofibroblasts earlier than the proliferation of endothelial cells, and endothelial cells also participated in the transformation and formation of mesenchymal cells; in order to explore whether the Zn2SiO4 extract interferes with the communication between fibroblasts and endothelial cells, the present invention used the supernatant of fibroblasts to treat endothelial cells and carried out scratch and migration experiments.
[0144] The scratch test was the same as in part (6) of Example 7; migration test: endothelial cells HUVECs (3×10 4Cells / well) were suspended in low-serum (0.1% fetal bovine serum) DMEM medium, and 300 μL per well were inoculated in a 24-well plate embedded with a chamber with a pore size of 8 μm (FALCON, USA); 300 μL of hypoxia-activated fibroblast supernatant or hypoxia-activated fibroblast supernatant treated with Zn2SiO4 extract (containing 20% fetal bovine serum) was added to the outer chamber as the experimental group and placed in a three-gas incubator, and the outer chamber of the normal group was high-concentration serum (20% fetal bovine serum) DMEM complete medium; the groups were Ctrl group (blank control); 1% O2 group (endothelial cells were treated with the supernatant of activated fibroblasts); 1% O2+Zn2SiO4 group (endothelial cells were treated with the supernatant of activated fibroblasts treated with Zn2SiO4). After 24 hours of culture, the migration chamber was taken out, and the cells adhering to the surface of the chamber filter were removed. The chamber was washed with PBS three times, each time for 5 minutes; the chamber was placed in a 24-well plate and fixed with 4% paraformaldehyde, and then washed with PBS three times, each time for 5 minutes; the lower surface of the chamber filter was stained with 0.1% crystal violet for 15 to 30 minutes, and then washed with DD water. The endothelial cells passing through the chamber were observed under an optical microscope, and the number of migrated cells was measured using Image J.
[0145] The scratch test results show that Fig. 22 ), the scratch healing area of endothelial cells in the 1% O2 group was smaller than that in the Ctrl group; while the 1% O2+Zn2SiO4 group could reverse the decrease in the scratch healing area of endothelial cells. Fig.23 ), the number of endothelial cell migration in the 1% O2 group was less than that in the Ctrl group; while the 1% O2+Zn2SiO4 group could reverse the decrease in the number of endothelial cell migration. These two experimental results indicate that the addition of Zn2SiO4 extract interferes with the communication between fibroblasts and endothelial cells and promotes the proliferation and migration of endothelial cells.
[0146] In summary, the above results show that Zn2SiO4 extract inhibits the proliferation and activation of fibroblasts by interfering with the cell cycle, inhibiting the fibrotic response of fibroblasts and inhibiting endothelial-mesenchymal transition.
[0147] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. Application of Zn2SiO4 in the preparation of drugs for treating and / or preventing ventricular aneurysms.
2. A zinc-containing bioceramic hydrogel precursor, characterized in that: The zinc-containing bioceramic hydrogel precursor comprises gelatin-hyaluronic acid hydrogel precursor and Zn2SiO4; Wherein, the gelatin is unmodified gelatin or photosensitive gelatin; the hyaluronic acid is unmodified hyaluronic acid or photosensitive hyaluronic acid; and at least one of the gelatin and hyaluronic acid is a photosensitive material.
3. The zinc-containing bioceramic hydrogel precursor according to claim 2, characterized in that: The photosensitive gelatin includes methacrylated gelatin.
4. The zinc-containing bioceramic hydrogel precursor according to claim 2, characterized in that: The photosensitive hyaluronic acid includes methacryloyl hyaluronic acid.
5. The zinc-containing bioceramic hydrogel precursor according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: fully mixing gelatin-hyaluronic acid hydrogel precursor gel and Zn2SiO4 under light-proof conditions to obtain the hydrogel.
6. The zinc-containing bioceramic hydrogel precursor according to claim 5, characterized in that: The mixing ratio of Zn2SiO4 and gelatin-hyaluronic acid hydrogel precursor is (20-30): 1 mg / mL.
7. The zinc-containing bioceramic hydrogel precursor according to claim 5, characterized in that: The mass ratio of the gelatin to the hyaluronic acid is (5-10):
1.
8. A zinc-containing bioceramic hydrogel, characterized in that: The zinc-containing bioceramic hydrogel comprises gelatin-hyaluronic acid hydrogel and Zn2SiO4 loaded therein; Wherein, the gelatin is unmodified gelatin or photosensitive gelatin; the hyaluronic acid is unmodified hyaluronic acid or photosensitive hyaluronic acid; and at least one of the gelatin and hyaluronic acid is a photosensitive material.
9. The method for preparing the zinc-containing bioceramic hydrogel according to claim 8, characterized in that: The method comprises the following steps: subjecting the zinc-containing bioceramic hydrogel precursor gel according to any one of claims 2 to 7 to a photo-crosslinking reaction under ultraviolet light irradiation to obtain the zinc-containing bioceramic hydrogel.
10. Use of the zinc-containing bioceramic hydrogel precursor gel according to any one of claims 2 to 7 or the zinc-containing bioceramic hydrogel according to claim 8 in the preparation of a drug for treating and / or preventing ventricular aneurysm.